Analisis Peran Ganda dalam Produktivitas Tenaga Kerja Wanita di PT Pelindo III Cabang Gresik - Siska Febriyanti; Maulidyah Amalina Rizqy (Universitas Muhammadiyah Gresik, 2021)
Background - Women's labor have multiple roles and must be able to balance work and household. Female workers who have a level of work-family conflict will have an impact on their ability to fulfill their jobs. Objective - This research aims to analyze the dual role in women's labor productivity in pelindo III Gresik Branch office. Design/Methodology/Approach - This study uses qualitative approach, the subject of this study is a female workforce of 12 people. Findings - Based on the results of the study, it can be concluded that female workers who have multiple roles continue to carry out their jobs well so that they are able to complete their duties properly. Research implications - This research can be used as consideration for the company in accepting female employees who already have a role in the household. Research limitations - This study has limitations on the factors behind women choosing to work and have a household.